A Novel Model Based on Spatial and Morphological Domains to Predict the Origin of Premature Ventricular Contraction - He, Kaiyue; Sun, Jian; Wang, Yiwen; Zhong, Gaoyan; Yang, Cuiwei (Frontiers in Physiology, 2021)
Pace mapping is commonly used to locate the origin of ventricular arrhythmias, especially premature ventricular contraction (PVC). However, this technique relies on clinicians’ ability to rapidly interpret ECG data. To avoid time-consuming interpretation of ECG morphology, some automated algorithms or computational models have been explored to guide the ablation. Inspired by these studies, we propose a novel model based on spatial and morphological domain. The purpose of this study is to assess this model and compare it with the three existing models. The data are available from the Experimental Data and Geometric Analysis Repository database in which three in-vivo premature ventricular contraction patients are included. To measure the hit rate (A hit occurs when the predicted site is within 15 mm of the target) of different algorithms, 47 target sites are tested. And to evaluate the efficiency of different models in narrowing down the target range, 54 targets are verified. As a result, the proposed algorithm achieves the most hits (37/47) and fewest misses (9/47). And it narrows down the target range most, from 27.62±3.47 mm to 10.72±9.58 mm among 54 target sites. It is expected to be applied in the real-time prediction of the origin of ventricular activation to guide the clinician towards the target site.